Cellular Signal Transduction Pathways Involved in Acute Lung Injury Induced by Intestinal Ischemia-Reperfusion. (4th June 2021) - Li, Guangyao; Zhang, Yingyi; Fan, Zhe
Abstract : Intestinal ischemia-reperfusion (II/R) injury is a common type of tissue and organ injury, secondary to intestinal and mesenteric vascular diseases. II/R is characterized by a high incidence rate and mortality. In the II/R process, intestinal barrier function is impaired and bacterial translocation leads to excessive reactive oxygen species, inflammatory cytokine release, and even apoptosis. A large number of inflammatory mediators and oxidative factors are released into the circulation, leading to severe systemic inflammation and multiple organ failure of the lung, liver, and kidney. Acute lung injury (ALI) is the most common complication, which gradually develops into acute respiratory distress syndrome and is the main cause of its high mortality. This review summarizes the signal transduction pathways and key molecules in the pathophysiological process of ALI induced by II/R injury and provides a new therapeutic basis for further exploration of the molecular mechanisms of ALI induced by II/R injury. In particular, this article will focus on the biomarkers involved in II/R-induced ALI.